Efficient retroviral infection of mammalian cells is blocked by inhibition of poly(ADP-ribose) polymerase activity. - Gäken, J; Tavassoli, M; Gan, S; Vallian, S; Giddings, I; Darling, D; Galea-Lauri, J; Thomas, MG; Abedi, H; Schreiber, V; Ménissier-de Murcia, J; Collins, M; et al. (1996)
Integration of proviral DNA into the host cell genome is a characteristic feature of the retroviral life cycle. This process involves coordinate DNA strand break formation and rejoining reactions. The full details of the integration process are not yet fully understood. However, the endonuclease and DNA strand-joining activities of the virus-encoded integrase protein (IN) are thought to act in concert with other, as-yet-unidentified, endogenous nuclear components which are involved in the DNA repair process. The nuclear enzyme poly(ADP-ribose) polymerase (PARP), which is dependent on DNA strand breaks for its activity, is involved in the efficient repair of DNA strand breaks, and maintenance of genomic integrity, in nucleated eukaryotic cells. In the present work, we examine the possible involvement of PARP in the retroviral life cycle and demonstrate that inhibition of PARP activity, by any one of three independent mechanisms, blocks the infection of mammalian cells by recombinant retroviral vectors. This requirement for PARP activity appears to be restricted to processes involved in the integration of provirus into the host cell DNA. PARP inhibition does not affect viral entry into the host cell, reverse transcription of the viral RNA genome, postintegration synthesis of viral gene products, synthesis of the viral RNA genome, or the generation of infective virions. Therefore, efficient retroviral infection of mammalian cells is blocked by inhibition or PARP activity.